2009
DOI: 10.1159/000237221
|View full text |Cite
|
Sign up to set email alerts
|

8-OHdG in Cerebrospinal Fluid as a Marker of Oxidative Stress in Various Neurodegenerative Diseases

Abstract: Background: The 8-hydroxy-2 deoxyguanosine (8-OHdG) is a product of nucleoside oxidation of DNA and a reliable marker of oxidative stress markers. Increased levels of oxidative stress have been reported in the cerebrospinal fluid (CSF) of patients with various neurodegenerative disorders. Objective: In search of a biochemical indicator of Parkinson’s disease (PD), we analyzed the levels 8-OHdG in the CSF of 99 patients, using ELISA to assess the differences between various neurodegenerative disorders. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 67 publications
(53 reference statements)
1
37
1
Order By: Relevance
“…16,21,22 Interestingly, in other studies, 8OHdG was elevated in leukocytes in Alzheimer disease and in urine in Friedreich ataxia 30,31 and was higher in CSF from patients with Parkinson disease without dementia than in controls, but there were no differences between levels in controls and those with Parkinson disease without dementia, Alzheimer disease, or dementia with Lewy bodies. 32 Furthermore, 8OHdG was higher in CSF, urine, and plasma from patients with amyotrophic lateral sclerosis compared with controls, whereas only the plasma levels and not the urine or CSF levels were elevated in a group of participants with other neurologic disorders. 33 Identification and validation of biomarkers for HD clinical trials is extremely important and remains a challenging goal; this was a principal goal of the prospective, longitudinal, observational TRACK-HD study.…”
mentioning
confidence: 82%
“…16,21,22 Interestingly, in other studies, 8OHdG was elevated in leukocytes in Alzheimer disease and in urine in Friedreich ataxia 30,31 and was higher in CSF from patients with Parkinson disease without dementia than in controls, but there were no differences between levels in controls and those with Parkinson disease without dementia, Alzheimer disease, or dementia with Lewy bodies. 32 Furthermore, 8OHdG was higher in CSF, urine, and plasma from patients with amyotrophic lateral sclerosis compared with controls, whereas only the plasma levels and not the urine or CSF levels were elevated in a group of participants with other neurologic disorders. 33 Identification and validation of biomarkers for HD clinical trials is extremely important and remains a challenging goal; this was a principal goal of the prospective, longitudinal, observational TRACK-HD study.…”
mentioning
confidence: 82%
“…However, immunoassays for measurement of 8-OHdG and F2-isoP have been criticized, although results employing this technology being widely published. [26][27][28] Recent publications critiquing ELISA-based 8-OHdG methods suggest that ELISA-based values tended to be higher values than ''gold-standard'' LC/ MS-based measurement. 29 However, several steps were taken in this trial protocol to reduce sources of variability that should have improved the ability to detect a trend for change, if one was present.…”
Section: Figmentioning
confidence: 99%
“…TAC includes antioxidant activities of non-enzymatic low molecular weight substances such as glutathione, ascorbic acid, uric acid, α-tocopherol, and coenzyme Q (Alho et al, 1998; Bartosz, 2003); a reduction in TAC could alter the balance between ROS levels and mechanisms which protect against their cytotoxic effects, in favor of oxidative damage. The concentration of 8-OHdG has been reported to be increased in PD cerebrospinal fluid (CSF) (Kikuchi et al, 2002; Abe et al, 2003; Gmitterová et al, 2009; Isobe et al, 2010). We found no reports of 8-ISO or TAC measurements in PD CSF; however, 8-ISO in the PD SNC has been reported to be unchanged (Fessel et al, 2003), while TAC in the PD SNC is reported to be decreased (Sofic et al, 2006).…”
Section: Introductionmentioning
confidence: 99%